2013
DOI: 10.1016/j.jecp.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The cost of selective attention in category learning: Developmental differences between adults and infants

Abstract: Selective attention plays an important role in category learning. However, immaturities of top-down attentional control during infancy coupled with successful category learning suggest that early category learning is achieved without attending selectively. Research presented here examines this possibility by focusing on category learning in infants (6–8 months old) and adults. Participants were trained on a novel visual category. Halfway through the experiment, unbeknownst to participants, the to-be-learned ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…These developmental changes transpire in a variety of tasks, including visual selection and visual search (Plude, et al, 1994), rule use (Hanania & Smith, 2010), classification (L. Smith & Kemler, 1977), and category learning (Best, Yim, & Sloutsky, 2013; Deng & Sloutsky, 2016). …”
mentioning
confidence: 99%
“…These developmental changes transpire in a variety of tasks, including visual selection and visual search (Plude, et al, 1994), rule use (Hanania & Smith, 2010), classification (L. Smith & Kemler, 1977), and category learning (Best, Yim, & Sloutsky, 2013; Deng & Sloutsky, 2016). …”
mentioning
confidence: 99%
“…For example, Best, Yim, and Sloutsky (2013) found that, in contrast to adults who attended selectively to relevant dimensions in category learning and exhibited evidence of learned inattention, 6- to 8-month-old infants attended to both relevant and irrelevant dimensions, and they did not exhibit learned inattention. Furthermore, in a recently published study, Deng and Sloutsky (2015b) demonstrated that diffused attention is an important property in early category learning: more successful learning in 8- to 12-month-old infants was accompanied by more distributed attention among different features of presented objects.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Best et al (2013) presented 6–8-months-old infants and adults with a two-phase category learning task, such that the dimensions that were relevant in the first phase became irrelevant in the second phase. Results indicated that although both groups learned categories, their patterns of allocating attention differed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence that successful category learning in 6–8-months-old infants is accompanied not by increased attention to commonalities (which is often the case in adults), but by broader exploration of features and thus more broadly distributed attention (e.g., Best, Yim, & Sloutsky, 2013). This prediction is based on a substantial body of literature demonstrating that distributed attention (with shorter individual fixations and frequent gaze shifts) is generally associated with better learning in infancy (e.g., Bronson, 1991; Colombo et al, 1991; Jankowski et al, 2001; Rose et al, 2003).…”
Section: Effects Of Words and Other Features On Category Learning In mentioning
confidence: 99%
“…This finding suggests that dynamic visual features (especially those that appear peripherally) may encourage distributed attention, thus facilitating learning. Given that successful category learning in infancy is also accompanied by distributed attention (e.g., Best et al, 2013), it is possible that such dynamic visual features may also affect infant category learning.…”
Section: Effects Of Words and Other Features On Category Learning In mentioning
confidence: 99%